PENERAPAN FUZZY LOGIC DALAM SISTEM PEMANTAUAN VITAL SIGN BERBASIS INTERNET OF THINGS - Rahmatulloh, Muhammad Rafy; Indroasyoko, Narwikant; Khoirunnisa, Hilda (The Indonesian Journal of Computer Science, 2024)
The development of the Internet of Things (IoT) has brought innovations in healthcare, especially in vital sign monitoring, crucial for detecting physiological changes and supporting disease diagnosis. Outpatient vital sign monitoring is often neglected due to time and equipment constraints. Previous research, such as using Bluetooth technology, showed range limitations, while other solutions couldn't classify patient conditions. This study develops an IoT-based vital sign monitoring device with four parameters: blood pressure, body temperature, heart rate, and oxygen saturation, accessible online. The device uses fuzzy logic to classify patient status. Test results show accuracy rates of 96.4% and 91.3% for blood pressure, 98% for heart rate, 98% for oxygen saturation, and 98% for body temperature readings. Patient classification tests showed 9 out of 10 samples had the same risk output as the NEWS assessment.